In-vitro Evaluation of Bio-control agents against Soil Borne Plant Pathogens - Manandhar, Shrinkhala; Pant, Bimala; Manandhar, Chetana; Baidya, Suraj (Journal of Nepal Agricultural Research Council, 2019)
Biocontrol is an important aspect of disease management for plant pathogens, especially for the soil borne fungi. Trichoderma species is the most exploited biocontrol agent in recent years. The soil specific nature of Trichoderma species is a well-known fact and hence native Trichoderma isolates should be more emphasized for control of plant pathogens. Fifty soil samples from rhizosphere of various agricultural crops were collected for isolation of Trichoderma sp. Ten isolates of Trichoderma were tested in dual culture with soil borne pathogens Fusarium solani, Rhizoctonia solani and Sclerotinia sclerotiorum in an in vitro assay. All of the test isolates were found to be significant in terms of mycelial inhibition growth as compared to control. However, varying degrees of antagonism by different Trichoderma isolates were observed for above mentioned soil borne pathogens. The isolate (T363) was found to exhibit more than 80% inhibition of S. sclerotiorum while the isolate T357 was found to control F. solani by more than 80%. For the control of R. solani, six of the tested Trichoderma isolates showed more than 80% inhibition of its radial colony growth. The Trichoderma isolates seen effective in this study need to be tested in pot and field experiments for exploiting the use and benefits of biocontrol.